The Crisis for Young People: Generational Inequalities in Education, Work, Housing and Welfare - Andy Green (Palgrave Macmillan, 2017)
This book provides an original and challenging analysis of one of the most pressing social issues of our times: intergenerational inequality. Based on recent mixed-method research, it explores the extent and scope of generational divides through an up-to-date analysis of the changing opportunities for young people in Britain across different life domains. A central question addressed is whether current changes are best understood as growing inequalities within and across age groups, or whether we face a genuine intergenerational decline over the life course of this and future generations of youth. Andy Green$1 (Bs controversial manifesto for intergenerational equity includes replacing higher education fees with a tax on graduates of all ages; the introduction of capital gains tax on sales of first homes; voting at 16, and a new charter of rights for private tenants.s
English
Keywords: NEET; education; widening participation